Genetic Diversity of Durian (Durio Zibethinus Murr.) in Nias Island, North Sumatera Use Random Amplified Polymorphic Dna (Rapd) Markers - Hannum, Saleha (International Journal of Ecophysiology, 2022)
Durian (Durio zibethinus Murr.) is one of tropic fruits that has varian taste depending on the places of their production. Nias Island, well known as durian production place in North Sumatera. The information about it’s varian was less studied and now day we need that information to analyze variant of durian especially in Nias Island. The aim of this research was to analyze genetic diversity of durian in Nias Island with Random Amplified Polymorphic DNA (RAPD). Ten shoots of durian was collected from each 5 regencies, which were: Nias Selatan, Nias Barat, Nias Utara, Nias Kota, dan Nias Induk. Durian’s DNA has been isolated by using Cetyl Trimethyl Ammonium Bromide (CTAB) method and amplified with six RAPD primers namely: OPA 01, OPA 03, OPA 07, OPA 10, RAPD 05, and OPN 06. The amplified band were scored and translated to biner data, then analyzed using Numerical Taxonomy and Multivariate System (NTSys) and clustered by Unweighted Pair Group Method With Arithme Average (UPGMA) method. Isolated DNA showed a clear and unsmeared band. The size of amplified band was around 221-2855bp with 100% of polymorphism. The dendogram was constructed by 50 accession of Nias’s durian with 0.51-0.59 of similarity value in each population. All of Nias’s durian accession has similiar value of 67% and B2 (Nias Barat) as a farthest genetic distance from all accession.